2006
DOI: 10.2172/887075
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 2 mrad and 14/20 mrad Crossing Angle Extraction Lines

Abstract: A study of the beam distributions in the 2 mrad and 14/20 mrad extraction lines are presented. Beam losses, energy losses due to synchrotron radiation and spin diffusion are shown. Synchrotron radiation distributions generated by the beam as it traverses the extraction lines are studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The luminosity weighted polarization at IP is approximated by [13,14]: (1) where θ angle (IP) is angle of a particle as it leaves the IP:…”
Section: Luminosity Weighted Polarization At Ipmentioning
confidence: 99%
“…The luminosity weighted polarization at IP is approximated by [13,14]: (1) where θ angle (IP) is angle of a particle as it leaves the IP:…”
Section: Luminosity Weighted Polarization At Ipmentioning
confidence: 99%
“…Distributions of positions, energy and angles at the Compton Detector Plane are shown. Previous studies of the14 mrad extraction line are found in reference [6]. Disrupted beam distributions were generated using Guinea-Pig code [4].…”
Section: Beam Studiesmentioning
confidence: 99%
“…This "tail" data set is extracted from ~17.5·10 6 particles in the full generated beam to provide a much higher beam tail statistics for the beam loss calculation. The low energy tail of the disrupted beam in the low power option cs14 was also studied corresponding to total 17.45·10 6 beam particles. There are 0.0096% lost particles between the e + e − IP and the Compton detector plane (an additional 0.00005% are lost between the Compton detector plane and z = 195 m).…”
Section: Beam Studiesmentioning
confidence: 99%